Ex Vivo and In Vitro Studies on the Cytotoxicity and Immunomodulative Properties of Poly(2-isopropenyl-2-oxazoline) as a New Type of Biomedical Polymer - Kroneková, Zuzana; Mikulec, Marcel; Petrenčíková, Nadežda; Paulovičová, Ema; Paulovičová, Lucia; Jančinová, Viera; Nosál', Radomír; Reddy, Palem S; Shimoga, Ganesh D; Chorvát, Dušan; Kronek, Juraj (Macromolecular bioscience, 2016)
Poly(2-alkenyl-2-oxazoline)s are promising functional polymers for a variety of biomedical applications, such as drug delivery systems, peptide conjugates, or gene delivery. In this study, poly(2-isopropenyl-2-oxazoline) (PIPOx) is prepared through free-radical polymerization initiated with azobisisobutyronitrile. Reactive 2-oxazoline units in the side chain support an addition reaction with different compounds containing a carboxylic group, which facilitates the preparation of polymers labeled with two different fluorescent dyes. The cytotoxicities of 2-oxazoline monomers, PIPOx, and fluorescently labeled PIPOx are evaluated in vitro using an 3-(4,5-Dimethyldiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay and ex vivo using a cell proliferation assay with adenosine triphosphate bioluminescence. The cell uptake of labeled PIPOx is used to determine the colocalization of PIPOx with cell organelles that are part of the endocytic pathway. For the first time, it is shown that poly(2-isopropenyl-2-oxazoline) is a biocompatible material and is suitable for biomedical applications; further, its immunomodulative properties are evaluated.
Keywords: fluorescence; Animals; proliferace buněk; 3T3 Cells; oxazoly; organely; Organelles; biokompatibilní materiály; slezina; functionalization of polymers; biocompatibility; Fibroblasts; splenocytes; Polymers; poly(2-isopropenyl-2-oxazoline); Oxazoles; Mice; Immunomodulation; fibroblasty; Mice, Inbred BALB C; fluorescenční spektrometrie; myši; buněčná smrt; endocytóza; Biocompatible Materials; myši inbrední BALB C; Polypropylenes; Cell Death; buňky 3T3; Spleen; Cell Proliferation; polymery; Endocytosis; Cell Survival; polypropyleny; zvířata; Microscopy, Confocal; viabilita buněk; konfokální mikroskopie; cell proliferation; imunomodulace; Spectrometry, Fluorescence